Investigation of Hydrogen Flow Uniformity in a Serpentine Separator Plate of a PEMFC Using Computational Fluid Dynamics Simulation - Wahyu, Haifa; Oemry, Achiar; Djunaedi, Imam (LIPI Press, 2012)
This paper presents an investigation on the uniformity of hydrogen flow in a separator plate of a Polymer Electrolyte Membrane Fuel Cell (PEMFC). Hydrogen is the main reactant of a PEMFC that fl ows within the separatorplate and into the MEA. Separator plates have fl ow fi eld lay out which is the determining factor for the uniform distribution of the gas. The separator plates used in this study has the shape of serpentine fl ow fi eld, taken from a 200 Watt PEMFC stack. The fl ow of hydrogen gas is simulated within the separator plate to analyse the pressure and velocity distribution which has a correlation with the fl ow fi eld design. The objective of the study is to determine flow uniformity within the separator plates by increasing the hydrogen gas pressure from 1 bar up to 3 bars. Although flow distributions for the three cases are similar and quite uniform, but the velocity in the plates was reduced when the hydrogen pressure was increased. This is due to the backpressure occurs as a result of resistance from the flow field and also the gas diffusion layer governing a fuel cell. From the experiments on the characterization of fuel cell stack, the best practice is to maintain the inlet pressure at low level, that is around 1 bar, which is in agreement with the current simulation results. The fl ow was simulated using commercial CFD package by employing Navier-Stokes method which is the governing equation of the computational fl uid dynamics (CFD) application. The results are compared to the steady output without random differences of an experimental running of the fuel cell stack.